Are conventional microbiological diagnostics sufficiently expedient in the era of rapid diagnostics? Evaluation of conventional microbiological diagnostics of orthopedic implant-associated infections (OIAI) - Aamot, Hege Vangstein; Noone, J Christopher; Skråmm, Inge; Leegaard, Truls M (Acta Orthopaedica, 2020)
Background and purpose — In a time when rapid diagnostics are increasingly sought, conventional procedures for detection of microbes causing orthopedic implant-associated infections (OIAI) seem extensive and time-consuming, but how extensive are they? We assessed time to (a) pathogen identification, (b) antibiotic susceptibility patterns, and (c) targeted antibiotic treatment using conventional microbiological diagnostics of OIAI in a consecutive series of patients. Patients and methods — Consecutive patients aged ≥18 years undergoing first revision surgery for acute OIAI, including prosthetic joints, fracture, and osteotomy implants, in 2017–2018 at Akershus University Hospital (Ahus), Norway were included. Information regarding microbiological diagnostics and clinical data was collected retrospectively from the hospital’s diagnostic and clinical databases. Results — 123 patients fulfilled the inclusion criteria. Median time to pathogen identification was 2.5 days and to antibiotic treatment recommendations was 3.5 days. The most common pathogens were S. aureus (52%) and S. epidermidis (15%). Cultures were inconclusive in 11% of the patients. Of the 109 patients with culture-positive results, antibiotic treatment was changed in 66 (61%) patients within a median of 4 days (0–24) after the recommendation was given. Interpretation — Conventional microbiological diagnostics of OIAI is time-consuming, taking days of culturing. Same-day diagnostics would vastly improve treatment efficacy, but is dependent on rapid implementation by clinicians of the treatment recommendations given by the microbiologist.